Role Playing Method on Arabic Speaking Skill (Maharah Kalam) - Basri, Dewi Jumrahwati; Hasmawati, Hasmawati; Ulum, Fatkhul (Interference: Journal of Language, Literature, and Linguistics, 2024)
Abstract. The research is a pre-experiment quantitative research with one group pre-test post-test design which aims to determinate the effectiveness of Role Playing method on Arabic speaking skills (Maharah Kalam) of fifth grade students of Madrasah Ibtidaiyah Fatthu Rahman Makassar. The population and samples in this study were all fifth grade students of Madrasah Ibtidaiyah Fatthu Rahman Makassar which amounted to 24 students using total sampling technique. The basis of the research results was obtained by giving oral pre-test and post-test with the material "Address" and "It's a Holiday". The results of hypothesis testing using the Wilcoxon Signed Rank Test show that the Asymp.Sig (2-tailed) is 0.000 which is then compared with the significance level of 0.05. The value of 0.000 is smaller than 0.05, thus H0 is rejected or H1 is accepted, so it can be stated that the Role Playing method is effective in learning Arabic speaking skills (Maharah Kalam) for fifth grade students at Madrasah Ibtidaiyah Fatthu Rahman Makassar. Keywords: Effectiveness, Role Playing, Arabic Speaking Skills